Penerapan Model Pembelajaran Berbasis Budaya Cerita Mitos Manarmakeri (CMM) untuk Menguatkan Sikap Antikorupsi - Patma Tuasikal; Luluk Nurrokhmah; Maria Kablesa (Universitas Muhammadiyah Mataram, 2026)
This research aims to test the effectiveness of the Cultural Marmakery Model (CMM) in improving students' anti-corruption attitudes. A quantitative approach with a quasi-experimental pre-test-post-test control group design was used. The population consists of students at Samber High School. Using purposive sampling, two classes with a total of 64 students were selected, with 32 students assigned to the experimental group and 32 to the control group. Data was collected through an anti-corruption attitude questionnaire given before and after the intervention and analyzed using descriptive and inferential statistics. Pre-test results showed comparable basic attitudes, with a mean score of 52.45 for the experimental group and 53.10 for the control group. After the intervention, the experimental group's average score increased to 82.60, while the control group reached 64.25. The experimental group experienced an increase of 30.15 points, compared to an increase of 11.15 points in the control group. Learning mastery was achieved by 87.50% of students in the experimental group, compared to 37.50% in the control group. These findings indicate that the Cultural Mythology Model effectively improves students' anti-corruption attitudes by integrating local cultural values into learning, strengthening integrity, honesty, responsibility, and social responsibility, while encouraging meaningful character development among secondary school students.